Marine interfaces ecohydrodynamics - Nihoul, Jacques C. J. (Elsevier oceanography series, 1986)
These proceedings describe physical and biological observations (including remote sensing observations) made at such diverse marine ergoclines as pynoclines, fronts, water-sediment and water-ice interfaces in different locations and environmental conditions. Mathematical models are described which are used to investigate the phenomena, providing a common language for their interpretation and the bases of the ecohydrodynamic study of marine interfaces.